2019
DOI: 10.1051/shsconf/20197006010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing of use of the Internet for personal reasons at lessons at school: A Validation of the Cyberloafing Scale

Abstract: Emergence of a possibility of Internet access at school bears new opportunities and risks too. The tendency to growth of number of the pupils Internet use for non-class-related purposes in the classroom (Cyberloafing) causes concern. Studying of this new phenomenon at the Russian school is complicated due to the lack of reliable and valid techniques. Therefore, adaptation of a scale of a cyberloafing of Y. Akbulut, etc. became an objective of this research. We translated into Russian of 29 items of a technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The scale used within the scope of this study was a five-factor scale consisting of 30 items -namely sharing (nine items), shopping (seven items), real-time updating (five items), accessing online content (five items), and gaming/gambling (four items), originally used to measure participants' cyberloafing levels, samples of which are included in Appendix A. The original five-factor scale was developed and validated by Akbulut et al (2016), and used successfully in several studies (e.g., Akbulut et al, 2017;Dursun et al, 2018;Gökçearslan et al, 2018;Kian-Yeik, 2018;Wu et al, 2018;Sivrikova et al, 2019). In the scale's original state, items within the same dimension were grouped together one after the other.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…The scale used within the scope of this study was a five-factor scale consisting of 30 items -namely sharing (nine items), shopping (seven items), real-time updating (five items), accessing online content (five items), and gaming/gambling (four items), originally used to measure participants' cyberloafing levels, samples of which are included in Appendix A. The original five-factor scale was developed and validated by Akbulut et al (2016), and used successfully in several studies (e.g., Akbulut et al, 2017;Dursun et al, 2018;Gökçearslan et al, 2018;Kian-Yeik, 2018;Wu et al, 2018;Sivrikova et al, 2019). In the scale's original state, items within the same dimension were grouped together one after the other.…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…Recently, the focus of research has shifted to the positive aspects of this behaviour. Researches have shown that cyberloafing behaviour reduces stress, improves mood, promotes self-development, increases motivation and develops the ability to multitask (Andel, Kessler, Pindek, Kleinman & Spector, 2019;Ozcan et al, 2017;Saleh, Daqqa, AbdulRahim & Sakallah, 2018;Sivrikova, Roslyakova, Sokolova & Moiseeva, 2019) In addition, the researchers note that due to the widespread use of cyberloafing, opportunities should be sought for the most effective combination of personal and work tasks (Burleson & Greenbaum, 2019).…”
Section: Cyberloafingmentioning
confidence: 99%
“…The scale proposed by Akbulut et al was used to collect empirical data about the level of adolescents' cyberloafing. The scale was translated into Russian and adapted (Sivrikova et al, 2019). It allows one to evaluate the frequency of manifestations of five types of cyberloafing behaviour during training sessions (Sa -Communication; So -Shopping; Aoc -Content; Gg -Gaming; Rtu -Social networks).…”
Section: Instrumentsmentioning
confidence: 99%
“…Research has shown that cyberloafing behavior exists in a modern school. However, its distribution depends on the quality of Internet technologies in the country and on their use in school [13,23,29]. Researchers point out that in schools, different types of cyberloafing behavior can be observed in school students sometimes or rarely.…”
Section: Cyberloafing In the Academic Spherementioning
confidence: 99%